Pharmaceutical waste management: sources, environmental impacts, and sustainable solutions - Baroka, Ima Uzni (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2025)
Pharmaceutical waste represents a growing global environmental and public health challenge requiring urgent attention across healthcare systems worldwide. This review examines the sources, environmental impacts, and management strategies for pharmaceutical waste based recent studies across six continents. Healthcare facilities generate the largest volumes of pharmaceutical waste, with hospitals producing 1,150-5,967 grams daily and specialized units contributing disproportionately high amounts. Community and household sources add significant distributed waste through improper disposal practices, with up to 95% of households maintaining unused medication inventories. Environmental impacts include widespread contamination affecting 96% of disposal pathways inappropriately, creating multiple exposure routes through terrestrial (49%), drainage (21%), and aquatic systems (25%). Antimicrobial resistance development represents a critical consequence, with 60% of environmental bacterial isolates demonstrating extended-spectrum β-lactamase production. Effective management strategies encompass source reduction achieving 1.9 kg CO2-equivalent climate benefits annually, hospital recycling programs generating 415,000 net value while diverting 461,000 medication units from incineration, and advanced treatment technologies reducing antibiotic concentrations to 0.002-0.68 mg/kg in recovered materials. Implementation success requires integrated approaches combining prevention, technology solutions, stakeholder engagement, and regulatory frameworks. Urgent action is needed to establish comprehensive pharmaceutical waste management systems that protect environmental and public health while achieving economic sustainability.